ANALISIS KERUSAKAN KOMPONEN FINAL DRIVE CATERPILLAR EXCAVATOR 329 DL - Razi, Misru; Munawir, Munawir; Khalik, Abdul; Arwin, Arwin (ELEMEN : JURNAL TEKNIK MESIN, 2025)
The purpose of the research is to analyze the functional final drive components to increase torque. To find out more in-depth about how to fix the damage to the final drive. This study uses a field observation method by making direct observations by looking for the cause of damage, and how to overcome damage to the final drive components, and conducting and question-and-answer method so that the problem that occurs in the final drive is found. Damage to the final drive of the CAT 329 DL excavator is due to this unit traveling a long distance. As a result, the input shaft components on the final drive are worn out, causing damage that results in noise on the front of the final drive when running. The input shaft component is damaged and must be replaced with a new one; if left unchecked, it will cause damage to other components. Damage to the input shaft makes the track unable to move. Components present in the planetary gear